Analysis of the Implementation of the Port Guard Service to Improve the Security and Safety of the KM. AWU Ship - Jane Alice Maharani; Anak Agung Istri Sri Wahyuni; Indah Ayu Johanda Putri; Anak Agung Ngurah Ade Dwi Putra Yuda (International Journal of Science and Environment (IJSE), 2026)
Port watchkeeping is an important activity in ensuring the security and safety of a vessel while it is berthed at the port, as it involves not only technical operational aspects of the ship but also supervision of passengers, luggage, and access to and from the vessel. This study aims to analyze the effectiveness of port watchkeeping implementation on KM. AWU and to identify efforts to improve safety and security while the vessel is in port. The research method used is a qualitative approach with data collection techniques through observation during sea practice, interviews, and documentation, which were then analyzed descriptively. The results show that the implementation of port watchkeeping on KM. AWU has generally been carried out quite effectively, particularly in technical safety aspects such as checking mooring lines and berthing conditions, monitoring vessel stability (draft, trim, and ballast), and inspecting berth lights and signals. However, preventive supervision of passengers and their belongings as well as recording activities in the watchkeeping log book still needs to be improved. In conclusion, the implementation of port watchkeeping has complied with procedural requirements but still requires improvement in preventive supervision aspects. Preventive measures that can be implemented include increasing patrol frequency during busy conditions, conducting active and scheduled CCTV monitoring, tightening supervision of access to and from the vessel, and ensuring that log book records are written in detail and comprehensively.